Models of religious solidarity among various beliefs in Sabah, Malaysia / Mohd Nazmi Mohd Khalli ... [et al.] - Mohd Khalli, Mohd Nazmi; Sintang, Suraya; Mohd Khambali @ Hambali, Khadijah; Marinsah, Syamsul Azizul; Abdul Rahman, Nur Farhanah (Universiti Teknologi MARA, 2021)
This article describes the current question that reflects the Sabahan communities who love peace and hate hostility in inter-community relations of different religions. The essence of religious solidarity reflected through the togetherness of different religious communities is one of the manifestations of Malaysian society's attitude that loves peace and hates enmity. The focus of this discussion was explained through the mixed-faith families and integrated relationship between the local communities of other faiths found around Sabah. The research was based on interviews, text content analysis, and field observations. The results show the function of religion as a strong catalyst of social integration which triggers the spirit of solidarity. This is clearly described through the attitude of togetherness within the intercommunity relations in Sabah that comfortably opt for peace and reject hatred and enmity. As this attitude is rooted in the values of patriotism, nationalism, and sense of belonging which are included in al-tadamun and al-takaful, the Sabahan society is often described as tolerant, easy to accommodate, and open in facing situations and challenges among believers of different religions. This study concludes that religious solidarity needs to be nurtured to ensure continued harmony in the Malaysian community.